Factors Influencing Foreign Visitors Perceptions And Intention To Revisit Palestine: The Case Of Bethlehem And Ramallah - Suleiman, Ja'far Subhi Hardan (2011)

(untitled)
The tourism industry is an important support for future economic growth in Palestine. It has major sacred sites for three main religions Islam, Judaism and Christianity. Bethlehem district has most religious and heritage places that attract numerous international visitors and also Ramallah city. Destination characteristics including political instability and perceived risk, destination image and revisit intention are essential factors in understanding tourism performance and the success of a country’s tourism industry.